The Effect of Immersion Time and Drying Method on The Colour of Canarium Nuts (Canarium vulgare Leenh) - Meittycorfrida Mailoa; Abraham H Tulalessy (Pattimura University Ambon Maluku Indonesia, 2021)
This study aimed to evaluate the resulting discoloration through a combination of immersion times and different drying methods. The design used in this study was a completely randomized design arranged in a factorial experiment with four replications. The first factor was immersion time, i.e., no immersion; immersed for 24 hours; immersed for 48 hours; while the second factor was drying methods, including without drying; drying in direct sunlight; drying by smoking, and drying by roasting in the sand. The research data were processed using the SPSS program using one-way ANOVA analysis by design. The Tukey test on treatments that were significantly different at a 95% confidence level. The results showed that: 1). Canarium nut without drying (fresh) produces a color (L) with a higher brightness level compared to the color of canarium nut from drying, smoking, and roasting; 2). Immersion for up to 48 hours did not result in significant changes to the color component; and 3) the change in color components was relatively small among the three different drying methods, namely drying in direct sunlight, smoking, and roasting.